A Robust and Scalable High-Throughput Compatible Assay for Screening Amyloid-β-Binding Compounds - McClure, Richard (J Alzheimers Dis, 2019)
A robust fluorescent readout assay using topologically-sensitive dyes improves the screening of novel amyloid-binding molecules. One of the key components that make this assay more realistic is the use of endogenous amyloid obtained from 5XFAD mouse brains. The assay conditions were optimized for high throughput screening operation with Z-prime values >0.6. Using a combination of library of 3,500 compounds including known drugs, natural-derived molecules and random organic molecules, 8 unique molecules were identified as potential amyloid-binding agents.